Enhancing Empathy and Tolerance in Social Studies Learning through Internet-Based Media: A Case Study at Moahino Elementary School - Sukma Sukma; Sunarto Amus; Nuraedah Nuraedah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study addresses the urgent need to foster empathy and tolerance in Social Studies (IPS) learning, especially within the Proclamation of Independence theme often neglected in traditional teaching. It aims to examine the effectiveness of internet-based media in developing these social values among fifth-grade students at SDN Moahino. Using a descriptive qualitative design, the study involved 10 students, a homeroom teacher, the principal, and several subject teachers selected purposively. Data were gathered through observations, interviews, and documentation over two learning cycles and analyzed using the Miles and Huberman model with triangulation for validity. Results showed that in the first cycle, the use of internet media had little impact on students’ attitudes, while in the second cycle, significant improvement occurred. Students exhibited higher empathy—respecting teachers, helping peers, and giving praise—and greater tolerance by cooperating without discrimination, avoiding bullying, and appreciating others’ opinions. The study concludes that internet-based media, particularly educational videos, effectively enhance empathy and tolerance when applied systematically and aligned with character education. Broader and more creative use of digital content is recommended to strengthen values-based learning in elementary schools.